National Parks Management and Conservation - Nazip Suratman, Mohd (IntechOpen, 2018)
The rapid fragmentation and habitat change in natural environments have created a need for management and conservation, which will ensure areas are protected from anthropogenic interference. These protected areas are necessary to provide adequate location for biodiversity conservation, environmental monitoring, and scientific research where a complete understanding of the natural process and full protection of ecosystems can be attained. This book highlights various approaches for managing and conserving protected areas in temperate and tropical regions to respond to some pressing global challenges today. It is divided into five main sections, viz., protected area management, fish and wildlife conservation, biodiversity conservation, ecotourism and recreation, and local community participation. The book enhances the understanding of the important roles national parks play in the environment and society.